2014
DOI: 10.1590/0102-33062014abb3436
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and mycorrhizal colonization in three species of epiphytic orchids in southeast Mexico

Abstract: Orchids establish symbiosis with Rhizoctonia mycorrhizal fungi, forming the characteristic pelotons within the cells of the root cortex. Under natural conditions, terrestrial and epiphytic orchids have different levels of dependence upon the fungal symbiont, although various authors have mentioned that once orchid plants reach maturity the interaction becomes weaker and intermittent. Recent evidence shows that in some epiphytic orchid species mycorrhization is constant and systematic. In three species of wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The percentage of fungal colonization in orchid roots also varies according to the root types. Bertolini et al (2014) demonstrated that mycorrhization is meticulously extant in orchid roots and it is dependent on the wet and dry seasons.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of fungal colonization in orchid roots also varies according to the root types. Bertolini et al (2014) demonstrated that mycorrhization is meticulously extant in orchid roots and it is dependent on the wet and dry seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Transversal root segments of approximately 2 mm were cut and sterilized by serial ethanol baths (Otero & Bayman 2009. Roots segments were examined for the presence of pelotons with a dissecting microscope at a 4X magnification, measuring the % of the total root section occupied by fungi following previously published methods (Bertolini et al 2014). Root sections that showed presence of hyphae coils (pelotons) in their cells were placed in Petri dishes with autoclaved potato dextrose agar (PDA) medium at pH 5.8.…”
Section: Field Sampling and Morphological Identification Of The Fungamentioning
confidence: 99%
“…Many species in the Orchidaceae family are terrestrial and have subterranean roots or tubers, while over 70% of the members of this family are epiphytic (including lithophytic) and their roots are usually exposed on the surface of rocks or tree stems [26]. Similar with the terrestrial orchids, the epiphytic species also have persistently present OMF colonization in their roots [27]. Different plant taxa and their mycorrhizal fungi may have various physiological demands (e.g., in water and nutrition utilization) [28].…”
Section: Introductionmentioning
confidence: 99%